Pelatihan Instrumen Praktikum Mikrobiologi Pada Guru SMA di Kabupaten Jayapura, Papua - Lantang, Daniel; Rampa, Ester; Allo, Elisabeth P.; Menufandu, Herlina; Sinaga, Herlando (Jurusan Biologi FMIPA Universitas Cenderawasih, 2025)
Along with the advancement of science in the health sector, biology teachers in high school must understand microbiology, especially have the ability to provide practicum to students so that students have the ability in the field of microbiology. The low understanding of students about microbiology subjects is due to the absence of microbiology practicum in high school. This service is carried out by giving a pre test, skills training and mentoring to teachers so that their knowledge increases, after which a post test is carried out. the increase in teachers' knowledge can be seen from the pre and post test results. Teachers understand and understand microbiology practicum instruments.